PENGUATAN DEWAN KEHORMATAN PENYELENGGARA PEMILU DALAM PENEGAKAN HUKUM KODE ETIK PENYELENGGARA PEMILU - Rosidin, Utang (LITIGASI, 2024)
The Election Organizer Honorary Council as an institution formed to handle violations of the code of ethics of election organizers applies the principles of maintaining justice, independence, impartiality, and transparency in enforcing the rules or ethical norms that apply to all election organizers, as stipulated in Law Number 7 of 2017. The method used in this study uses a normative legal approach. The results of the study, First, the legal framework for handling violations of the code of ethics of election organizers in Indonesia is a mandate of Law Number 7 of 2017, in Article 1 number 24 which states that the Election Organizer Honorary Council is an institution tasked with handling violations of the code of ethics of Election Organizers. Second, The urgency of law enforcement for violations of the code of ethics of election organizers as an effort to present the integrity of election organizers is the main capital in realizing democratic elections, the presence of the Election Organizer Honorary Council as an institution that is given the authority to handle violations of the code of ethics of election organizers is important in order to realize election organizers with integrity. Third, the Election Organizer Honorary Council in the process of handling alleged violations of the code of ethics of election organizers can be carried out including by carrying out prevention, action, and innovation in various forms of activities carried out in the process of law enforcement against alleged violations of the code of ethics of election organizers.